Body window-enabled in vivo multicolor imaging of transplanted mouse islets expressing an insulin-Timer fusion protein. (October 2003) - Bertera, Suzanne; Geng, Xuehui; Tawadrous, Zakaria; Bottino, Rita; Balamurugan, A.N.; Rudert, William A.; Drain, Peter; Watkins, Simon C.; Trucco, Massimo
Type 1 diabetes results from the selective destruction of insulin-producing β cells in the islets of Langerhans, and autoimmune T cells are thought to be the mediators of this destruction. T cells are also responsible for allorejection once the islets are transplanted into a patient to reduce the negative consequences of a lack of insulin. To better understand these processes, we have developed a transgenic mouse expressing proinsulin II tagged with a live-cell fluorescent reporter protein, Timer. Timer protein is unique because it changes color from green to red in the first 24 h after synthesis. With this marker, insulin synthesis can be carefully monitored through fluorescent changes over time. To complement this new biotechnological research tool, we designed a body window to allow for in vivo imaging over time of the islets transplanted under the kidney capsule. The window device, which is sutured to replace the underlying skin and body wall over the site of islet transplantation, may be used to simultaneously observe β cells and T cells that have been labeled with a fluorochrome distinguishable from Timer. The imaging of both insulin-producing cells and T cells may be carried out repeatedly for a week or more with no need for repeated surgery, while preserving the life of the studied animal.